Role of family dynamics in shaping adolescent social behavior and mental health: A health sociology perspective - Baso Witman Adiaksa; Muhammad Syukur (Jurnal Ilmiah Kesehatan Sandi Husada, 2025)
Introduction: Family dynamics play a crucial role in shaping adolescent social behavior and psychological health. Adolescence is a critical developmental stage marked by rapid physical, emotional, and social changes. During this period, family communication, emotional support, and parental involvement significantly influence the formation of social values and mental well-being. Methods: This study employed an analytical survey design using a cross-sectional approach to examine the role of family dynamics in shaping social behavior and psychological health among students of SMA Negeri 15 Wajo. A total of 65 adolescents were selected through purposive sampling. Data were collected using a structured questionnaire developed by the researchers and analyzed using Chi-Square tests with a significance level of α = 0.05. Results: The findings revealed a statistically significant relationship between family dynamics and both behavioral problems and psychological health (p = 0.002). Adolescents from families with positive dynamics exhibited better social behavior and mental health outcomes compared to those from families with poor communication and emotional conflict. The univariate analysis also showed that most respondents experienced supportive family environments (83.1%) and good psychological health (73.8%). Conclusion: Healthy family dynamics contribute positively to adolescents’ behavioural development and psychological stability. Effective communication, emotional warmth, and balanced parental involvement serve as protective factors against deviant behaviors and mental health disorders. Future research should further explore sociocultural aspects influencing these relationships to support interventions promoting adolescent well-being.